Agricultural service delivery during turmoil: The state of agricultural extension and crop advisory services in Myanmar - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
Access to agricultural extension and crop advisory services can play a crucial role in ensuring widespread and appropriate use of new and improved agricultural technologies, but the delivery and use of such services is not well understood in Myanmar. We assess their use based on repeated large-scale and nationally representative farm surveys from 2020 onwards, as well as on insights from key informant interviews and secondary data. The major findings are the following: 1. Agricultural extension use is low and declining. Before the crisis years – due to COVID-19 and a military coup – agricultural extension provision and use in Myanmar was at much lower levels than in neighboring countries. There has been a further decline in use since. Forty-one percent of farmers reported to have received crop advice during the monsoon of 2020, but this share declined by 9 percentage points to 32 percent of farmers in the monsoon of 2022. 2. In-person agricultural extension is more widely used than digital extension. In the last dry season, 26 and 20 percent of the farmers relied on in-person and digital extension respectively. 3. The private sector is the main provider of in-person agricultural extension. During the last dry season, the main provider of in-person agricultural extension was the private sector (used by 18 percent of the farmers), followed by the public sector (13 percent of the farmers), and NGOs (6 percent). Previous seasons show similar shares. 4. In-person agricultural extension has been declining since 2020. In the last three years, there has been a significant decline in the provision of in-person extension services by all providers. In the case of the public sector in particular, the number of agricultural extension events in 2021/22 dropped by more than 50 percent compared to before the crisis years. 5. Digital agricultural extension service provision increased rapidly before 2020. Before the COVID-19 pandemic and the political crisis, the provision of digital extension services grew rapidly, linked to the rapid expansion of mobile cellphone networks and the spread of cheap smart phones. The total number of posts on Facebook by agricultural companies and organizations from July 2015 until November 2019 more than tripled. The biggest growth in posts was seen in 2018 and 2019, before the COVID-19 pandemic. 6. Digital agricultural extension provision decreased immediately after the coup, but then expanded again in the years after. It was used by 20 percent of the farmers during the last dry season. Most users started using digital agricultural extension since the COVID-19 pandemic and the political crisis. After the initial drop in 2021 - as the use of Facebook was banned and as there were severe communication blockages - there has been an increase in activity since, and this has occurred despite the persistent communication and internet problems and reduced mobile network access in the country. 7. Digital agricultural extension is mostly provided through Facebook by agricultural input companies and social enterprises. The most widely used services are provided through Facebook pages, that for a number of organizations and companies have millions of followers. An analysis of the posts on these Facebook pages shows they contain more technical information than product advertisements, even so for (almost) all commercial input retail companies. We also recently note the establishment of farmer extension groups – a more interactive model – and specific commodity focused groups on Facebook. There are also groups on other online platforms, including specialized agricultural apps and call centers. However, these platforms are less used. Digital extension services are almost exclusively provided by the private sector, including social businesses. 8. Use of agricultural extension is non-inclusive, with less educated, more remote, female, and smaller farmers accessing them less, for digital as well as for in-person extension. We also note an important difference by age, with older farmers relying more on in-person services and younger ones more on digital extension. 9. Conflict-affected areas access agricultural extension services significantly less frequently. Farmers residing in townships under martial law – 13 percent of the townships – use any extension (in-person or digital) service less (8 percent compared to townships not under martial law, often because they lack access to the internet in these townships). While farmers residing in the most insecure areas use in-person extension less (11 percent less), they are however able to rely on digital services to a similar extent as farmers in the more secure townships.